PENGARUH TINGKAT KESULITAN KEUANGAN, MEKANISME GOOD CORPORATE GOVERNANCE, DAN KUALITAS KANTOR AKUNTAN PUBLIK TERHADAP KONSERVATISME AKUNTANSI - Frida Putri Novianti; Astohar Astohar (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2015)
This study aims to examine the effect of the level of financial distress,corporate governance mechanisms and the quality of public accounting firmsto accounting conservatism. Accounting conservatism is the dependentvariable in this study is measured by the size of the accrual. Independentvariables measured include levels of financial distress, managerialownership,institutional ownership, the proportion of independent board,board size, audit committees, the number of partners who have permissionaccountants and public accounting firms size. The control variables in thisstudy are firm size and leverage.The populationof thisresearchis a property companylistedinIndonesiaStock Exchange (IDX) in 2009 to 2011. The total study sample was 31companies determined through purposive sampling. Useful analysis of data isdone with the classical assumption and hypothesis testing with multiplelinear regression method. The results of this study indicate that board sizeand firm size control variable positive influence on conservatism.Institutional ownership, audit committees and the quality of the publicaccounting firm based partner who has a negative effect on accountantlicense conservatism. For the level of financial difficulty, managerialownership, the proportion of independent board, the size of the firm and thecontrol variables do not leverage positive influence on conservatism.